2011
DOI: 10.1111/j.1468-3083.2010.03824.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of vitiligo in children and adolescents by autologous cultured pure melanocytes transplantation with comparison of efficacy to results in adults

Abstract: The satisfactory results obtained in the treatment of vitiligo in children and adolescents by transplantation of cultured autologous pure melanocytes are comparable with the results in adults. Therefore, this procedure can be considered in refractory and stable vitiligo in children and adolescents, especially in patients with large vitiliginous lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 27 publications
2
23
0
Order By: Relevance
“…Clinically, transplantation of autologous melanocytes therapy is proven to be the most effective therapy option for the vitiligo patients [14], [15], [16]. Groups including ours have treated vitiligo patients using this method with the cure rate above 53% [14], [15].…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Clinically, transplantation of autologous melanocytes therapy is proven to be the most effective therapy option for the vitiligo patients [14], [15], [16]. Groups including ours have treated vitiligo patients using this method with the cure rate above 53% [14], [15].…”
Section: Introductionmentioning
confidence: 93%
“…Groups including ours have treated vitiligo patients using this method with the cure rate above 53% [14], [15]. Studies showed that the number of cytotoxic CD8+ T cells was higher in active disease than in stable disease [17].…”
Section: Introductionmentioning
confidence: 97%
“…Melanocytes were isolated and cultured by methods based on those described previously (16,17). Primary melanocytes (passage 3–5) from vitiligo patients or normal controls were seeded into 6-well plates at a density of 1×10 5 cells/well and kept in an incubator for 4 h to allow them to attach.…”
Section: Methodsmentioning
confidence: 99%
“…A number of dermatosurgery techniques are available to promote repigmentation of vitiligo in adults and children, such as mini- or punch grafts, split-thickness skin grafts, cultured epidermal sheets, cultured melanocyte suspensions, follicular grafts and suction blister grafts. [718] Among these methods, the highest success rates have been achieved with split-thickness skin grafts and epidermal blister grafts. For better results, phototherapy or photochemotherapy of donor sites can also be performed after or before grafting.…”
Section: Introductionmentioning
confidence: 99%